Learning WordPerfect 6 : step by step - Kumar, Chandra (Kuala Lumpur : Venton Pub., 1994)
WordPerfect is among the most popular word processing programs available today. Much of this popularity is due to its very powerful features. Although WordPerfect 6 is easy to learn, many first-time users don't have the time to study the manuals which come with the program. This book is written for such users, people who want to start producing documents with WordPerfect 6 in the quickest time possible.